Ergotism associated with minimal dose of Ergotamine tartrate in HIV patient treated with antiviral protease inhibitor: case report - Taksaudom, Noopon (Biomedical Sciences and Clinical Medicine, 2014)
Ergotism is a rare cause of vasospasm caused by ergot-alkaloid intoxication or pharmacokinetic interactions. We report a case of a 30-year-old HIV positive male patient on protease inhibitors, who developed ergotism under the co-treatment of headache by ergot-alkaloids. The HIV-positive population receiving antiviral therapy may be an underrecognized group at risk for ergotism through drug-drug interaction via Cytochrome P-450 pathway.